Toward smart net zero energy structures: Development of cement-based structural energy material for contact electrification driven energy harvesting and storage. (November 2021) - Ra, Yoonsang; You, Ilhwan; Kim, Minchang; Jang, Sunmin; Cho, Sumin; Kam, Dongik; Lee, Seung-Jung; Choi, Dongwhi
Abstract: As the buildings and infrastructures are considered as the most crucial target for developing an energy zero smart city, the concept of the net zero energy structure (NZES), which can harvest renewable energy and offset the energy consumption, has been considered as an integrated solution. Herein, a strategy for harvesting and storing energy using cement-based conductive composite (CBC) with carbon fiber fillers as structural energy material is suggested. Simultaneous consideration of electrical and mechanical properties of CBC results in the optimal concentration as its electrical percolation threshold ( 1 vol%) to take sufficient long-range electrical conductivity while minimizing the deterioration of the mechanical property. The CBC introduced triboelectric nanogenerators, CBC-TENGs, are developed to demonstrate the harvesting various renewable energies, such as the wind, biomechanical, and blue energies, and the practical using of it. Moreover, the CBC-capacitor, which employs CBC as the core element of the capacitor, is fabricated to show the potential of CBC as a member in the structural capacitor. Given that cement is the most ordinary but indispensable one among the constructing materials, CBC has a great potential in the development of the NZES and in realizing the energy zero smart city based on the excellent functionalities of CBC. Graphical Abstract: ga1 Highlights: Propose of cement-based conductive composite (CBC) based net zero energy structure. Use of carbon fiber fillers in CBC to develop structural energy material. Generate electricity from triboelectricity assisted structural energy harvesting with CBC. Store harvested energy in a structural capacitor with CBC.